David Copperfield - Dickens, Charles 1812-1870. (New York : Macmillan, 1962)
Metro-Goldwyn-Mayer completes "David Copperfield". Pictures of some of the leading players in the screen version of "David Copperfield" ... Lionel Barrymore as Dan Peggotty, Frank Lawton as David, Elizabeth Allen as David's mother, Roland Young as Uriah Heap ... novelist Hugh Walpole as the Vicar of Blunder Street and Edna May Oliver as Aunt Betsy Trotwood.
In: American theater programs of the late 19th and 20th centuries (Library of Congress).
Keywords: David Copperfield (Motion picture : 1935); Clippings -- Washington (D.C.) -- 1934.